Analisis Penerapan Analisis Standar Belanja (ASB) dan Standar Harga dalam Penyusunan Anggaran Daerah Kota Medan Tahun 2025 - Esra Novita Sinabutar; Grace Galatia Br.Manullang; Renny Maisyarah (Journal Social Society, 2026)
The effectiveness of regional budget preparation is an essential aspect of realizing transparent, accountable, and efficient public financial management. Therefore, this study aims to analyze the implementation of Analisis Standar Belanja (ASB) and Standar Harga in the preparation of the Regional Revenue and Expenditure Budget (APBD) of Medan City for 2025. The study examined three research variables, namely the implementation of Analisis Standar Belanja (ASB), the implementation of Standard Prices, and the effectiveness of APBD preparation. This study employed a quantitative approach using a cross-sectional survey design involving 120 accounting students from the Universitas Sumatera Utara, Universitas Negeri Medan, and Universitas Medan Area. Respondents were selected using purposive sampling, while data were collected through a five-point Likert scale questionnaire measuring the implementation of ASB, Standard Prices, and the effectiveness of APBD preparation. The collected data were analyzed using descriptive statistics and multiple linear regression analysis. The results indicate that the implementation of ASB has a positive and significant effect on the effectiveness of APBD preparation (? = 0.42; p < 0.001), while Standard Prices also have a positive and significant effect (? = 0.35; p < 0.001). The regression model produced an R² value of 0.48, indicating that 48% of the variation in APBD preparation effectiveness can be explained by these two variables. These findings confirm that the implementation of expenditure standards and standard prices plays an important role in improving the quality of regional budget planning. Therefore, local governments are encouraged to strengthen the implementation of these standards through socialization, training, and integration into operational financial planning procedures.